2010
DOI: 10.1111/j.1471-4159.2009.06553.x
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell‐secreted superoxide dismutase promotes cerebellar neuronal survival

Abstract: It has been postulated that bone marrow-derived mesenchymal stem cells (MSCs) might be effective treatments for neurodegenerative disorders either by replacement of lost cells by differentiation into functional neural tissue; modulation of the immune system to prevent further neurodegeneration; and/or provision of trophic support for the diseased nervous system. Here we have performed a series of experiments showing that human bone marrow-derived MSCs are able to protect cultured rodent cerebellar neurons, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 59 publications
6
102
0
Order By: Relevance
“…Importantly, MSCs express CD59, a complement regulatory protein, and also release complement factor H that protects them from complement lysis (Tu et al 2010;Moll et al 2011). In addition, stimulation through C3aR and C5aR protect MSCs from oxidative damage (Schraufstatter et al 2009) and MSCs produce a number of antioxidants including hemeoxygenase-1 and superoxide dismutase (Kemp et al 2010;Mougiakakos et al 2011), and have been shown to suppress oxidative stress and inflammation in ischemia reperfusion injury models in vivo (Chen et al 2011Sun et al 2011;Du et al 2012). The exact mechanisms of action are unclear; however, MSC protection in these models was associated with increased expression of IL-10, heme oxygenase-1 (HO-1), and hepatocyte growth factor, decreased expression of the proinflammatory cytokines IL-1b, TNF-a, and interferon g (IFN-g), reduced reactive oxygen species, reduced apoptosis and decreased numbers of activated T cells, and infiltrating immune cells (Hara et al 2011;Sun et al 2011;Chen et al 2012;Du et al 2012).…”
Section: Effect Of Mesenchymal Stromal Cells On Ischemia Reperfusion mentioning
confidence: 99%
“…Importantly, MSCs express CD59, a complement regulatory protein, and also release complement factor H that protects them from complement lysis (Tu et al 2010;Moll et al 2011). In addition, stimulation through C3aR and C5aR protect MSCs from oxidative damage (Schraufstatter et al 2009) and MSCs produce a number of antioxidants including hemeoxygenase-1 and superoxide dismutase (Kemp et al 2010;Mougiakakos et al 2011), and have been shown to suppress oxidative stress and inflammation in ischemia reperfusion injury models in vivo (Chen et al 2011Sun et al 2011;Du et al 2012). The exact mechanisms of action are unclear; however, MSC protection in these models was associated with increased expression of IL-10, heme oxygenase-1 (HO-1), and hepatocyte growth factor, decreased expression of the proinflammatory cytokines IL-1b, TNF-a, and interferon g (IFN-g), reduced reactive oxygen species, reduced apoptosis and decreased numbers of activated T cells, and infiltrating immune cells (Hara et al 2011;Sun et al 2011;Chen et al 2012;Du et al 2012).…”
Section: Effect Of Mesenchymal Stromal Cells On Ischemia Reperfusion mentioning
confidence: 99%
“…[73,74] Catalase in the medium can protect against H 2 O 2 generated both intracellularly and extracellularly, since H 2 O 2 readily crosses the cell membranes and so external catalase can "drain" H 2 O 2 out of the cell. [24] Sometimes compounds oxidize in cell culture media but do not generate H 2 O 2 .…”
Section: 24]mentioning
confidence: 99%
“…Another beneficial factor of mesenchymal stem cells is an anti-inflammatory effect. The upregulation of transforming growth factor beta 1, an antiinflammatory factor that controls cell proliferation and apoptosis, has been observed and significantly reduced oxidative stress (Chen et al, 2011;Hawryluk et al, 2012;Kemp et al, 2010;Whone et al, 2012). Unlike others, there are almost no allergic reaction in mesenchymal stem cells.…”
Section: Cell-based Interventionsmentioning
confidence: 93%